2015
DOI: 10.1016/j.carbon.2015.07.081
|View full text |Cite
|
Sign up to set email alerts
|

A computational study on the effect of local curvature on the adsorption of oxygen on single-walled carbon nanotubes

Abstract: a b s t r a c tWe investigated the effect of local curvature on the adsorption of oxygen on single-walled carbon nanotubes based on density functional theory calculations with van der Waals corrections. The results showed that as the curvature increases, the interaction of the nanotubes with oxygen increases as well. An oxygen atom was strongly chemisorbed on the bridge site of the nanotubes accompanied by a significant transfer of charge from the surface to the oxygen atom. Larger curvature enhanced both the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 45 publications
2
13
0
Order By: Relevance
“…1. Previous studies [20,21] indicated that adsorption energies are dependent on the local curvature of SWCNT, showing that adsorption energy is lowest when carbon-carbon bond orientation is along the tube axis, and is highest when the orientation is perpendicular to the tube axis, (in agreement with our findings, Table 1). Using Eq.…”
Section: Adsorption Sites and Energiessupporting
confidence: 93%
See 1 more Smart Citation
“…1. Previous studies [20,21] indicated that adsorption energies are dependent on the local curvature of SWCNT, showing that adsorption energy is lowest when carbon-carbon bond orientation is along the tube axis, and is highest when the orientation is perpendicular to the tube axis, (in agreement with our findings, Table 1). Using Eq.…”
Section: Adsorption Sites and Energiessupporting
confidence: 93%
“…Three equilibrium adsorption sites for carbon adatom were identified for a (5,5) SWCNT, close to the middle of the CNT length. In agreement with previous studies [20,22], they are located above the bridges connecting neighboring carbon atoms, as shown in Fig. 1(a).…”
Section: Adsorption Sites and Energiessupporting
confidence: 93%
“…These contradictory findings are perhaps obtained due primarily to differences between material characteristics and processing conditions of the nanocomposites. Furthermore, there are a number of other parameters such as the curvature of carbon nanotubes [133,134], which has been found to play a significant role in achieving the optimum performance of nanocomposites. However, the experimental results or even realistic modelling predictions have always been below the rule of mixtures predictions [135].…”
Section: Carbon Nanotube-polymer Interactions In Nanocompositesmentioning
confidence: 99%
“…[362] Both D3 and MBD have been shown to be very effective for many different types of problems, from ice cluster energies through crystal cohesion energies to basic chemistry and to surface adhesion to interactions with graphite and nanotubes. [260][261][262][263][264][265][266][267][268][269][270]341] This occurs despite fundamental limitations in the description of the interactions (Table 2). Success comes from the fact that these methods are designed to model interaction energies and geometries and are usually only applied for these purposes.…”
Section: à6mentioning
confidence: 99%
“…This includes a molecular n-bit shift register made by the controlled synthesis of large porphyrin assemblies on substrates containing leads fabricated using current silicon device technology. [259] The established synthetic strategies involve scanning tunnelling microscopy (STM)-induced reactions of molecules [260][261][262][263][264][265][266][267][268][269][270] on silicon surfaces performed with atomic precision, [271,272] that are subsequently linkable to porphyrins.…”
mentioning
confidence: 99%